Legislative and judicial responses to the “refugee crisis” in Slovenia and Austria - Kogovšek Šalamon, Neža (Dve domovini, 2023)
The article compares key normative and judicial responses to the 2015–2016 “refugee crisis” in Slovenia and Austria. It does so by comparing the asylum statistics, the main changes to the legislation reflecting populist reactions to the “refugee crisis,” and judicial responses to these changes and reactions. The qualitative legal analysis is based on examples of the most important changes and responses. The article considers the populistic context of these changes, as discussed by some political scientists, who demonstrate that with the crisis, a new wave of populism—“the populist Othering of migrants”—emerged.
Keywords: Austria; Avstrija; begunska kriza; constitutional court; populism; populizem; refugee crisis; Slovenia; Slovenija; ustavno sodišče